ANALISIS PELAKSANAAN FUNGSI BENDAHARA PEMERINTAH DAERAH SEBAGAI PEMUNGUT PPN DAN PPh PASAL 22 DI PROVINSI SUMATERA BARAT (Studi Kasus pada CV LPM, distributor motor roda tiga) - Charoline Cheisviyanny (InFestasi, 2015)
Abstract This research aimed to analyze the implementation of government treasurers’ role as the collectors of withholding tax (VAT and income tax 22). The object of the research was CV LPM, a distributor of tricycle motor in West Sumatera area, which often makes transactions with government. The research was a descriptive qualitative research which was held by analyzing the related documents and interviewing with finance and accounting division and marketing division. The result showed that there were some government treasurers which have not implemented their roles as the collectors of withholding tax. The constraints faced by the company were time constraint, administration constraint, and the problem of calculating the VAT base. It suggested : (1) for government treasurers, to implement their role strict to the rule, (2) for tax authority, to monitor the implementation of withholding system including the calculation of VAT base in vehicle trading, (3) for company, to understand the rule, and (4) for further research, to do the analysis from government and the procurement division’s point of view.